THE RELATIONSHIP OF HANDGRIP STRENGTH AND HAND DIMENSIONS IN ADOLESCENTS AGED BETWEEN 13-14 YEARS - Ali Işın; Çağhan Buğra Ödüz Ozus; Tuba Melekoğlu (ümit doğan üstün, 2018)
The purpose of this study was to examine the effect of hand dimension on handgrip strength in adolescents aged 13-14 years who do or not perform sports. A total of 56 adolescents (28 athletes and 28 non-athletes) aged between 13-14 years volunteered to participate in this study. Body length (cm), body weight (kg), body mass index (kg / m2), handgrip strength and hand dimension were measured. Hand dimension, length and handgrip measurements were taken from the dominant hand of the volunteers. After normality test, independent samples t test was used to analyse the difference between groups and Person Correlation was used to analyse the relationship between the groups via using SPSS v.24. As a result of this study, it was found that the handgrip strengths of the athletes were significantly higher than the non-athletes (p <.01). However, there were no significant differences between the hand dimensions of the athletes compared to the non-athletes. When the relationship between the hand dimension and the strength parameters was examined in adolescents, it was seen that as the hand length, the hand area, and the hand circumference increase, strength values also increase. There was a correlation between hand dimensions and handgrip strength values (p <.001).